Solving the modern marriage puzzle : the problems of creating value in marriage - Ang, Claudia Hui Lin (2017)
This paper argues that marriage should be disestablished, or at the very least, reformed. Marriage lacks intrinsic value, and if socioeconomic purposes that necessitated marriage in the past are no longer valid now, then there remains no good justification for marriage. This creates what I call the modern marriage puzzle. In a bid to solve this puzzle and to promote its own public policy goals, states attach extrinsic value to encourage people to marry. The Singapore government does this by providing housing incentives. However, this creates a host of social problems. First, the requirements of housing incentives encourage individuals to marry early even if they might lack the financial stability, maturity, and know-how to sustain their marriages. Second, the distribution of exclusive rewards to married couples breeds an environment of stigmatization and discrimination against the non-married demographic. I argue that while incentivizing marriage solves the modern marriage puzzle, it promotes irrational and morally problematic marriage decisions that threaten the well-being of not just the marrying agents themselves, but also the general non-married population peripheral to their marriages.